Seismic strengthening of RC columns using enhanced steel jacket. FE modeling (Journal of Civil Engineering Researchers, 2022)
This paper presents a new rectified square steel jacket for retrofitting of poorly confined reinforced concrete columnsin flexural plastic hinge regions. All of the analyses was carried out based on finite elements procedure. Having verifiedthe FE modeling, a deficient RC column designed according to pre-1971 codes was considered and eleven specimen withvarious detail of retrofitting were investigated. Effects of increasing at thickness of plate stiffeners, geometric shape ofstiffeners and stiffened length of jacketed column have been studied. The results obtained from the parametric studyindicated effectiveness of rectified jacket and allow a series of guidelines to be established.
Keywords: RC square column; seismic retrofitting; rectified steel jackets; finite element analysis; ductility; energy dissipation